Biosensor Based on the Immobilization of Laccase on β‐Cyclodextrin Membrane for the Evaluation of Antioxidant Capacity in Real Samples - Jorge Juárez‐Gómez; Omar Alejandro Báez‐Melga; Dafne Sarahia Guzmán‐Hernández (ChemistryOpen)
Abstract The optimization of a new amperometric biosensor for evaluating antioxidant capacity in real samples is reported. The biosensor is based on the immobilization of Laccase from Trametes versicolor on an electropolymerized β‐cyclodextrin polymeric membrane on a glassy carbon electrode. The process of electropolymerization, which was successful even in the presence of the enzyme, was a key step in biosensor synthesis. Variables such as pH, temperature, and enzyme concentration were optimized using a factorial design with two levels for each factor. Different electrodes were constructed and tested using caffeic acid as a standard. The best biosensor is synthesized at pH 3.0 with 6 mg/mL of enzyme and 30 °C. The biosensor presented a response time of ≤30 seconds and good stability in its amperometric response. The biosensor was used to evaluate the antioxidant capacity of real samples. Infusions of green, black, red, and white tea were assessed. The biosensor showed excellent stability and good performance regarding response time, stability, and easy fabrication. The proposed biosensor is a good option for evaluating antioxidant capacity in real samples without sample pretreatment. It combines a simple fabrication methodology and a minimal extraction process for rapid and reliable phenolic content determination in real samples.